The development of new industries in countries rich in natural resources: A comparison between the Norwegian and the New Zealand economies - Blom-Bakke, Arne (Auckland University of Technology, 2006)
In this dissertation I have made a comparison between the Norwegian and the New Zealand economy focused around new industry development in the two countries. The industry I have focused on is the aquaculture industry within the two countries as I see this industry having the potential of becoming a girder in both the countries economies. The reason for choosing these two countries comes down to the fact that there are several similarities between the two countries both in size, population and topography, as both have large fjords suitable for aquaculture. The aquaculture industry is an industry that has been experiencing a strong growth in Norway the recent decades and it is seen as a successor for the oil and gas industry within the country. Norway is today one of the world’s largest aquaculture countries and as I show in this dissertation the potential is there for New Zealand to achieve a similar position within the market. The first chapter gives an overview of the global development and growth of the aquaculture industry the last 30 years and the facts I have found and unveiled in this section will give the reader the understanding of the importance of this industry in the world today. The next two chapters give a historic view of the aquaculture industry within Norway and New Zealand, looking back at challenges and growth within the two countries. After reading these two chapters it becomes evident that the aquaculture industry has developed to a further extent in Norway than in New Zealand. In the final chapter I look at the future of the industry in New Zealand. I look back at how the industry has developed in Norway and look at how this development might be useful for New Zealand to draw upon when developing the aquaculture industry further in the country. As this industry is a relatively new industry changes within ownership, markets and production changes fast. In the last month several changes has occurred within the Norwegian industry with a large degree of mergers and acquisitions. As these changes not interfere with the historical development in Norway and the future expansion in New Zealand I have not brought it into contention. I still feel it is important to note that the person now acquiring several aquaculture companies within Norway is Norway’s richest man, John Fredriksen, who has made his wealth within shipping and oil services, industries that have both been of vital importance for the Norwegian economy. This makes the indication I made, towards the aquaculture industry being the future of the Norwegian economy, more suggestive. I have found great interest in writing this dissertation and hope the reader finds it just as interesting to read.
Keywords: Aquaculture industry -- New Zealand; Aquaculture industry -- Norway